Surviving Heart Failure: The Fatter the Better? - Vinall, Maria (MD Conference Express, 2010)
The 1999 consensus recommendations for heart failure (HF) stated that obese patients should lose weight [Am J Cardiol 1999], and according to data from the Framingham Heart Study, even being overweight poses an increased risk for HF (5% for men and 7% for women for each increment of 1 in body mass index) [Kenchaiah S et al. N Engl J Med 2002]. However, the current American College of Cardiology/American Heart Association Heart Failure Guidelines [Hunt SA et al. J Am Col Cardiol 2005; Jessup M et al. Circulation 2009] contain no mention of weight loss for HF patients. Why? This article discusses clinical trials why fatter may be better in heart failure.